2023
DOI: 10.1039/d3cp03305h
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the degradation mechanism of ibuprofen in the UV/H2O2 process: role of natural dissolved matter in hydrogen transfer reactions

Zhezheng Ding,
Jiahui Zhang,
Timing Fang
et al.

Abstract: Natural dissolved matter can significantly catalyze the degradation of ibuprofen during the UV/H2O2 process forming more toxic products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Studies have revealed that within a certain range, solvents can affect the microstructure of ILs and their properties. The surface tension of ILs is highly sensitive to slight changes in concentration. Therefore, understanding the variations in surface tension of mixtures is crucial. Researchers have employed experimental methods to investigate the interfaces of ILs and their mixtures. Abolfazl Shojaeian conducted a detailed measurement of the surface tension of aqueous solutions of three kinds of ILs ([C n mim][BF 4 ]). The system’s surface tension exhibited a pronounced inflection at low ILs concentrations, displaying a nonlinear trend.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that within a certain range, solvents can affect the microstructure of ILs and their properties. The surface tension of ILs is highly sensitive to slight changes in concentration. Therefore, understanding the variations in surface tension of mixtures is crucial. Researchers have employed experimental methods to investigate the interfaces of ILs and their mixtures. Abolfazl Shojaeian conducted a detailed measurement of the surface tension of aqueous solutions of three kinds of ILs ([C n mim][BF 4 ]). The system’s surface tension exhibited a pronounced inflection at low ILs concentrations, displaying a nonlinear trend.…”
Section: Introductionmentioning
confidence: 99%